Emprendimiento femenino y habilidades financieras en las microempresarias de la ciudad de Requena 2023 - Lavinto Hernández, Katerin (2023)
After considering as a general objective: to determine the relationship between female entrepreneurship and financial skills in micro-entrepreneurs of the city of Requena, 2023, where we worked with an applied type of research, descriptive-correlational level and non-experimental design, where it was taken as a sample. A questionnaire was applied to 70 microentrepreneurs to obtain information. Coming to the conclusion that the level of entrepreneurship is medium (23%), this situation is due to the feeling of indecision since the micro-entrepreneurs remain motivated and trust in their abilities; However, these skills are not always clear, these people are motivated by looking for new ways of doing things instead of focusing on known ideas. On the other hand, the development of financial skills is evaluated as "regular" (21%), the majority disagrees about using financial products such as credit cards or loans, and they strictly monitor their personal finances; Although they do understand their level of indebtedness somewhat and make decisions based on this information, it still needs to improve and they must take actions to achieve it. In general terms, it was determined that there is a positive and considerable relationship between the variables, corroborated by a Pearson coefficient of 0.801 and a significance of 0.000.